Munda languages are father tongues, but Japanese and Korean are not. (29th May 2020) - Chaubey, Gyaneshwer; van Driem, George
Abstract: Abstract: Over two decades ago, it was observed that the linguistic affinity of the language spoken by a particular population tended to correlate with the predominant paternal, i.e. Y-chromosomal, lineage found in that population. Such correlations were found to be ubiquitous but not universal, and the striking exceptions to such conspicuous patterns of correlation between linguistic and genetic phylogeography elicit particular interest and beg for clarification. Within the Austroasiatic language family, the Munda languages are a clear-cut case of father tongues, whereas Japanese and Korean are manifestly not. In this study, the cases of Munda and Japanese are juxtaposed. A holistic understanding of these contrasting cases of ethnolinguistic prehistory with respect to the father tongue correlation will first necessitate a brief exposition of the phylogeography of the Y chromosomal lineage O. Then triangulation discloses some contours and particulars of both long lost episodes of ethnolinguistic prehistory.